A Study of Reliability and Validity for Citizenship Knowledge and Skill Scale - Icen, Mustafa (IZZET KARA, 2020)
The study aims to develop a current scale that has a higher validity and reliability and reveals high school students' perceptions of measuring their citizenship knowledge and skills. The study was conducted with two different groups. The first group is the group where data is collected to conduct Exploratory Factor Analysis (EFA) and it consists of 258 students. The second group is the group where the data is collected to carry out Confirmatoty Factor Analysis (CFA) and it consists of 180 students. A total of 438 students participated in the study providing different students were in both groups. As a result of the analyzes it was determined that the Citizenship Knowledge and Skill Scale, which includes a total of 24 items, consists of a 5-factor structure. These factors are termed as Participation in Social Life, Right to Education, Individual Duties, Duties of the State and Common Rights. The total variance explained by the scale is 61.79%. Additionally, there is a significant relationship between these 5 factors and there is no atttocorrelation problem. Item-factor and item-test correlation coefficients were calculated for all items of the scale and it was determined that each item was consistent not only with the factor it contained but also with the whole test. Cronbach Alpha reliability of the general of Citizenship Knowledge and Skill Scale is 0.91 and Omega reliability is 0.92. It can be said that the reliability and validity of the scale are applicable and high.
Keywords: Citizenship; Social studies; Citizenship education; Reliability; Validity; EXPLORATORY FACTOR-ANALYSIS; MAXIMUM-LIKELIHOOD; PARALLEL ANALYSIS; FIT INDEXES; NUMBER; COMPONENTS; COMMON; INDICATORS; VALIDATION; EDUCATION; Education & Educational Research